(untitled) (Global Journal of Human-Social Science, 2021)
The purpose of this article is to argue that though there is a general perception that main black African female literary characters in the Sesotho novels published under the heyday of apartheid reflected the patriarchy and the racial subjugation of the time. This article demonstrates that in some Sesotho novels published during the apartheid era, the main literary characters had agency. In the Sesotho novel, Peo ena e jetswe ke wena, the central black female character, Samina is characterised as being rebellious to the patriarchal system. She is portrayed as independent and unmarried, and evil and devious. Her evil intentions are directed at destroying men she tempts as lovers.